Tuesday
March 28, 2017

Post a New Question

Posted by on .

Use the functions f(x)=1/8x-3 and
g(x)=x^3 to find the indicated value or function.

(g^-1 X f^-1)(-3)

  • Math - ,

    f^-1)(-3) is the value of x that you get when f(x) = -3. That value is 0.

    g^-1(0) is the value of x that you get when g(x) = 0. That is also zero.

    So (g^-1*f^-1)(-3) = 0

    In functional form,
    f^-1(x) = 8(x+3)
    g^-1(x) = x^(1/3)
    (g^-1*f^-1)(x) = [8(x+3)]^1/3
    2(x+3)^1/3

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question